Efectividad de procesos de eliminación de sangre en la desinfección de las Unidades de Atención Odontológica Unach, 2022 - Garofalo Gortaire, Jimpson Geovanny (2023)
ABSTRACT The dental care area represents a high-risk environment for cross-contamination, maintaining an environment free of any contaminant is essential in the context of disease control and prevention, because, due to its work, it is frequent to be in contact with saliva and/or blood of the patient. The objective of this research project is to evaluate the effectiveness of disinfection systems in the UAO UNACH on the elimination of blood, for this purpose the reagent luminol was used on a total of 42 surfaces including: backrest, dental chair seat, spittoons, chair lamps, among others, belonging to the UAO clinic I and II UNACH. The results showed a positivity for the presence of blood macules in 100% of the surfaces studied. Among these findings, the presence of projection type blood macules (drops or splashes) prevailed in 88.1% of the total cases. It also showed that the surfaces with the most macular contamination were the trash can, spittoon and chair backrest. Among the established findings, there was no major difference in blood macules revealed between clinics I and II, when these were apparently clean and decontaminated after their last use before the vacation period. Therefore, it is established that the disinfection methods used are not effective in the elimination of blood spots. Reviewed by: Lic. Alison Tamara Varela. ENGLISH PROFESSOR C.C. 0606093904